Environmental and spatial factors play different roles in phytoplankton community assembly in different hydrological seasons in Lake Wuchang, China - Meng, Zihao; Chen, Kang; Hu, Feifei; Liu, Lu; Yang, Deguo; Li, Xuemei (Frontiers in Ecology and Evolution, 2023)
Lake phytoplankton communities are affected by environmental and spatial factors. We studied the relative importance of environmental and spatial factors on the phytoplankton community assembly in Lake Wuchang across three hydrological seasons, which were divided into dry (December to March), normal (April to June, October to November) and wet seasons (July to September) based on the water level and depth. Results showed that phytoplankton assemblages at the eight study sites were composed of totally 244 species belonging to 9 phyla, which changed from Bacillariophyta and Chlorophyta to Cyanophyta across the whole hydrological period. There was significantly higher abundance and biomass in the normal and wet seasons than that in the dry season.Phytoplankton alpha diversity exhibited unanimous temporal distribution patterns with higher values in the dry season than in the normal and wet seasons. The Mantel and partial Mantel tests revealed that environmental (physicochemical conditions of lake water) and spatial factors (geographic distances among sites) jointly affected the phytoplankton community structure and beta diversity across the hydrological seasons, while spatial factors were more important in the wet season. Partial least squares path models showed that spatial factors exhibited a significant positive correlation with the phytoplankton diversity with the path coefficients of 0.53 and 0.71 in the normal and wet seasons, respectively. Phytoplankton composition had significant correlation with on phytoplankton diversity with the path coefficient of -0.75 and 0.61 in the normal and wet seasons, respectively. Our findings revealed that both environmental and spatial factors affected the phytoplankton community assembly in Lake Wuchang.Environmental factors played a more important role in the dry season, while spatial factors were more important in the wet season. In addition, the hydrological characteristics could also have an important impact on phytoplankton community assembly, thus there is a need to focus on ecological connectivity and species dispersal in future studies.Except for the abiotic factors (environmental and spatial), the impacts of biotic factors on phytoplankton community cannot be ignored. Therefore, it is also necessary to strengthen further research on the top-down control over phytoplankton communities in Lake Wuchang.